Prediksi Penjualan Produk Promo PT. Unilever, Tbk Menggunakan Metode Fuzzy Time Series - Yehoshua Yehoshua; Kustanto Kustanto; Retno Tri Vulandari (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
PT. Unilever is a multinational company headquartered in Rotterdam, the Netherlands (under the name Unilever N.V.), London, England (under the name Unilever pic.) And in Indonesia has a subsidiary, PT. Unilever, Tbk was established on December 5, 1933. Unilever produces food, drinks, cleaners, and also body care. Unilever is the third largest producer of household goods in the world, if based on the amount of revenue in 2012, behind P & G and Nestle. In forecasting products, it is often influenced by the sale of these products because there are also changes in sales for each period. Usually there is an increase in sales of these products which, among other things, is caused by price discounts, new products, one free one to buy promo, or a saving package from Unilever or from a rival company. Data collection method used by the author is a method of observation or directly observing the process of transmission, interview methods and literature study methods. While the method for processing data uses fuzzy time series algorithms, context diagrams, data flow diagrams, HIPO, relational diagram entities, data dictionary design, input design, output design, relation diagrams between tables, system implementation and testing. The method for implementation uses vb.net and Mysql. The results of this thesis are a system for calculating the forecasting amount of sales or sales of promo products for the following year. From this system, information on store data, item data, sales year history data, and forecasting data from fuzzy time series data will be displayed.. From rinso goods promotion data which have been calculated using fuzzy time series method which get MAPE value equal to 3,2%, so sales data for category of goods will experience increase based on calculation equal to 3,2%.